(untitled) (Journal of Hama University, 2025)
The study aimed to identify the level of moral judgment and to identify the difference in moral judgment according tow variables (gender and age) in a sample of students at the first basic education in Tartous city, the sample composed of (125) students, (83) males and (42) females. Researche used moral judgment scale by (Abd-AlFattah, 2002) The results of the study: the major of students exist in the second level of autonomy morality with(80.8%), as for the variable of age, there was a significant difference in moral judgment and for the older ones, while this difference did not appear between males and females